An Unexpected Cause of Raised Procalcitonin - Uzma Sabahat; Liza Mariam Thomas; Niaz Ahmed Shaikh; Nageen Murad Ali (Dubai Medical Journal)
A 28-year-old female was admitted to hospital with a history of paracetamol overdose, a total of 18 g, 2 days prior to presentation. Other than nausea and mild abdominal pain she had no other symptoms and systemic examination was unremarkable. Laboratory tests showed slightly elevated liver enzymes and significantly elevated procalcitonin level of 97 ng/mL (normal <0.05 ng/mL). This septic biomarker was alarmingly high, though the patient had no clinical features of infection, and C-reactive protein – the other routinely done marker of inflammation – was normal. She received treatment with N-acetylcysteine for paracetamol overdose. Other than slightly elevated liver enzymes, tests of liver function were essentially normal. All investigations for underlying infection were negative. She had a short uncomplicated 5-day hospital stay. Her procalcitonin levels improved spontaneously and were significantly reduced though not yet normal at the time of discharge.